Mechanisms of immune responses in juvenile Acanthopagrus latus to Aeromonas hydrophila infection revealed by multi-tissue transcriptomic analysis - Hong-Di Fan; Min Liu; Yuan-Ming Zhao; Xu Wang; Jia Lin; Qing Zhu; Wen Huang; Jiang-Hai Wang (Aquaculture Reports)
Yellowfin seabream (Acanthopagrus latus) is an economically important species extensively cultivated along the southeast coastal sea of China. This species is frequently afflicted by infections from Aeromonas hydrophila, a pathogen that causes widespread morbidity and mortality. In this study, an infection model was established by administering an intraperitoneal injection of A. hydrophila into yellowfin seabream. Subsequent observations and histopathological assessments revealed considerable damages of multi-tissues after the infection. Biochemical serum assays and measurements of immune-related enzyme activities indicated evident metabolic disturbances and inflammatory pathways in the affected fish. RNA sequencing analysis identified 1615 differentially expressed genes (DEGs) in the liver and 2578 DEGs in the intestine. KEGG mapping revealed significantly regulated pathways, including the C-type lectin receptor signaling pathway and MAPK signaling pathway in the liver, and calcium signaling pathway and cytokine-cytokine receptor interaction in the intestine. A protein-protein interaction network was also constructed for pivotal genes, such as cxcr4b and cd44b, which may play crucial roles in the immune and inflammatory pathways of yellowfin seabream. The transcriptomic results were further corroborated by quantitative real-time PCR tests of some specific genes. These novel data have revealed the immune-related pathways and key regulatory genes activated by A. hydrophila infection and may offer a valuable insight into the immune response mechanisms of yellowfin seabream.